2019
DOI: 10.1016/j.foodres.2018.09.016
|View full text |Cite
|
Sign up to set email alerts
|

CLA-producing adjunct cultures improve the nutritional value of sheep cheese fat

Abstract: The influence of the autochthonous CLA-producing Lactobacillus plantarum TAUL 1588 and Lactobacillus casei subsp. casei SS 1644 strains and the ripening time on the fatty acid (FA) content and sensory characteristics of sheep cheese were investigated. Three cheese types with different cultures and the control cheese were produced in duplicate and ripened for 8 months. 86 individual FA were determined by gas chromatography. Ripening time (2, 90, 180 and 240 days) did not have a significant effect (P > .05) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Nudda et al (2005), after examining a large number of milk and cheese samples, observed that the CLA levels in cheese reflect the composition of the raw milk used. Renes et al (2019) indicated that this could be because the cheese matrix provides stability to the bioactive fatty acids, perhaps preventing oxidation of these compounds during ripening.…”
Section: Cheese Fatty Acid Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Nudda et al (2005), after examining a large number of milk and cheese samples, observed that the CLA levels in cheese reflect the composition of the raw milk used. Renes et al (2019) indicated that this could be because the cheese matrix provides stability to the bioactive fatty acids, perhaps preventing oxidation of these compounds during ripening.…”
Section: Cheese Fatty Acid Profilementioning
confidence: 99%
“…Lin et al (1999) recorded the highest CLA levels in Cheddar cheese after 3 mo of ripening, and Buccioni et al (2010) reported that the total CLA content in Pecorino cheese increased by more than 10% during ripening. In a recent study (Renes et al, 2019), the presence of Lactobacillus plantarum and Lactobacillus casei ssp. casei CLA-producing strains led to a decrease in SFA content and to higher levels of VA, CLA, and n-3 (omega-3) fatty acids, compared with control cheese.…”
Section: Introductionmentioning
confidence: 96%
“…brevis and Weissella hellenica from selected Japanese fermented foods (Barla et al ., ). In addition, conjugated linolenic acid (CLNA) and conjugated linoleic acid (CLA) are among the fatty acids currently investigated from LAB strains in the production of functional beverages and food products (Renes et al ., ). Organic acids, carotenoids, glutathione and β‐glucan are among the yeast metabolites explored hitherto, and found to possess antioxidant properties (Balasubramanian & Ragunathan, ).…”
Section: Selection Of Starter Cultures Adjuncts and Microbial Communmentioning
confidence: 97%
“…It comes in a wide range of flavours, textures, and is primarily made from cow milk. Other milk types that have been used include those from buffalo (Bontempo et al, 2019;Da Silva et al, 2019), goats (Darnay et al, 2019;Leclercq-Perlat et al, 2019) and sheep ( Cipolat-Gotet et al, 2016;Derar and El Zubeir, 2014;Nguyen et al, 2019;Renes et al, 2019;). However, due to the high fat content of foods of animal origin and the consumers' awareness of the relationship between diet and health, there is a growing demand for vegetable milk such as soymilk with lower fat content.…”
Section: Introductionmentioning
confidence: 99%